SREBP1 regulates Lgals3 activation in response to cholesterol loading - Jing Li; Hongtao Shen; Gary K. Owens; Lian-Wang Guo (Elsevier, 2022)
Aberrant smooth muscle cell (SMC) plasticity is etiological to vascular diseases. Cholesterol induces SMC phenotypic transition featuring high LGALS3 (galectin-3) expression. This proatherogenic process is poorly understood for its molecular underpinnings, in particular, the mechanistic role of sterol regulatory-element binding protein-1 (SREBP1), a master regulator of lipid metabolism. Herein we show that cholesterol loading stimulated SREBP1 expression in mouse, rat, and human SMCs. SREBP1 positively regulated LGALS3 expression (and vice versa), whereas Krüppel-like factor-15 (KLF15) acted as a negative regulator. Both bound to the Lgals3 promoter, yet at discrete sites, as revealed by chromatin immunoprecipitation-qPCR and electrophoretic mobility shift assays. SREBP1 and LGALS3 each abated KLF15 protein, and blocking the bromo/extraterminal domain-containing proteins (BETs) family of acetyl-histone readers abolished cholesterol-stimulated SREBP1/LGALS3 protein production. Furthermore, silencing bromodomain protein 2 (BRD2; but not other BETs) reduced SREBP1; endogenous BRD2 co-immunoprecipitated with SREBP1's transcription-active domain, its own promoter DNA, and that of Lgals3. Thus, results identify a previously uncharacterized cholesterol-responsive dyad-SREBP1 and LGALS3, constituting a feedforward circuit that can be blocked by BETs inhibition. This study provides new insights into SMC phenotypic transition and potential interventional targets.